Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env150
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐Adapted Microorganisms: Adaptation Strategies and Biotechnological Potential

Abstract: Cold‐Adapted Microorganisms—Definition Ecology Mechanisms of Adaptation to Cold Biotechnological Potential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 103 publications
0
59
0
3
Order By: Relevance
“…During the past decade it has been recognized that cold-adapted microorganisms provide a wide biotechnological potential, offering numerous economic and ecological advantages over the use of organisms and their enzymes which operate at higher temperatures (Brenchley, 1996;Gerday et al, 2000;Margesin et al, 2002;Soriano et al, 2000). Cold-active enzymes are characterized by high catalytic effi ciency at low and moderate temperatures at which homologous mesophilic enzymes are not active, and are thermolabile (Margesin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade it has been recognized that cold-adapted microorganisms provide a wide biotechnological potential, offering numerous economic and ecological advantages over the use of organisms and their enzymes which operate at higher temperatures (Brenchley, 1996;Gerday et al, 2000;Margesin et al, 2002;Soriano et al, 2000). Cold-active enzymes are characterized by high catalytic effi ciency at low and moderate temperatures at which homologous mesophilic enzymes are not active, and are thermolabile (Margesin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the other end of the temperature scale, metabolically active psychrophilic bacteria have been detected in liquid brine veins of sea ice at Ϫ20°C (4). These cold-loving microorganisms face the thermodynamic challenge to maintain enzyme-catalyzed reactions and metabolic rates compatible with sustained growth near or below the freezing point of pure water (5,6). Directed evolution experiments have highlighted that, in theory, cold activity of enzymes can be gained by several subtle adjustments of the protein structure (7).…”
mentioning
confidence: 99%
“…Suutari and Laakso reported that at low temperature the ratio of unsaturated fatty acids to saturated fatty acids is increased in the membrane. It can modulate the activities of the enzymes involved in fatty acid and lipid biosynthesis [21] and help to synthesis the short-chain fatty acids, branched chain fatty acids and anteiso-fatty acids to long chain fatty acids, straight-chain fatty acids and iso fatty acids respectively [22]. Some investigators believed that cryoprotectants prevent the cold induced aggregation of proteins and maintain the optimum membrane fluidity even at low temperature.…”
Section: Cryo -Defense Strategy Of Marine Cold Loving Microorganismsmentioning
confidence: 99%
“…Thus the major drawback in the use of cold proteases for such purposes is their weak stability at temperatures higher than 25°C. However, in recent years with the growing interest on cold enzymes, researchers are focusing more on the thermal stability and molecular adaptation of these protein molecules [44,45]. Taguchi demonstrated that sequential random mutagenesis exhibited 70% higher catalytic efficiency in comparision with wild type at 10°C when Pro-L-Phe-p-nitroanilide was used as a synthetic substrate.…”
Section: Enzymes From Marine Cold Loving Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation